Avaliação da influência dos ângulos de flexão das limas no preparo do batente apical pelas técnicas de instrumentação manual e rotatória - Pereira, Analice Giovani (2011)
Introduction: The shaping ability of root canal instruments is often assessed in terms of preservation of the original root canal curvature without creating iatrogenic events. The aim of this study was to evaluate the influence of flexion angles produced by files during root canal instrumentation on the final form of apical stop. Methods: Sixty human lower incisors were divided into three groups (n=20). After coronal opening and tooth length measuring, radiographs were taken in two aspects (mesio-distal and buccal-lingual) with the files in working length. The flexion of files was evaluated from radiographs as the angle formed between the divergence of the file and its virtual image on its long axis. Teeth from group 1 were instrumented with stainless steel Flexofiles up to #40 file. For groups 2 and 3, Hand ProTaper Universal and ProTaper Universal rotary files were used respectively, up to file F4. New radiographs were taken for both aspects with a #15 K-file at working length. After gutta-percha insertion the specimen s apexes were ground allowing gutta-percha visualization and a picture was taken from the apex to identify root canal deformation with computer software. Results: Data showed that group 2 presented the highest variation in flexion angles compared to group 1 (0.112) and to group 3 (0.024) p<0.05. ProTaper Universal rotary system promoted lower apical stop deformation than the both manual techniques using NiTi (0.011) and stainless steel files (0.025) p<0.05. Conclusions: Force vectors caused by the flexion angles of files during the instrumentation of curved canals promoted apical stop deformation. Protaper Universal rotary files showed less apical deformation than hand ProTaper Universal and stainless steel files.